MICROBIOTA IN MICE CONSUMING FERMENTED LOTUS (Nymphaea pubescens) SEEDS - Iin Khusnul Khotimah; Rita Khairina (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2016)
The objective of this study was to evaluate microbiota in mice consuming fermented lotus seeds. There were two groups of mice studied, namely a group of mice given a standard diet (K), and a group of mice given standard ration added with fermented lotus seeds (TP). The parameters measured in the study were body weight of mice, total microbes, number of BAL, and number of E. coli, (14- and 28- day experiments). Each observation was repeated three times. The results showed that the consumption of fermented lotus seeds did not have any effect on microbiota (the number of microbes, BAL, and E. coli) in mice within the 28- day experiment, but the mice lost weight as much as 2.13%.